The estimation of exergy efficiency and exergy losses in air conditioning systems of operating cleanrooms by a Grassmann diagram - Harasym, Dmytro; Labay, Volodymyr (Lviv Polytechnic National University, 2015)
An important place in the up-to-date technologies related to energy transformation is occupied by the processes and equipment for which the objective value of energy perfection can be defined only on the basis of the thermodynamic analysis. The simplest method of thermodynamic analysis is the energy method based on the law of energy conservation. It provides the possibility to estimate the absolute and relative energy losses and to reveal equipment and processes with the highest losses. However, this method makes the values of all kinds of energy equal, thermal energy in particular, which is wrong according to the second law of thermodynamics, because any kind of energy can be completely converted into thermal energy, while the reverse process is accompanied by unavoidable losses. An innovative mathematical research model of an existing central straight-flow air conditioning system for operating cleanrooms is presented in this article. The aim of the model is to carry out computer estimation of exergy efficiency of existing air conditioning system and exergy losses of its elements depending on different factors affecting its work. The Grassmann diagram of exergy flows and losses for the existing air conditioning system at an outdoor air temperature of 35 °C has been defined due to this model. У сучасних технологіях, пов’язаних з перетворенням енергії, а саме у СКП, важливе місце займають обладнання і процеси, об’єктивну оцінку ступеня енергетичної досконалості яких можна встановити тільки на основі їх термодинамічного аналізу. Найпростішим методом термодинамічного аналізу є енергетичний, заснований на законі збереження енергії. Він дає змогу оцінити абсолютні і відносні втрати енергії, виявити обладнання і процеси з найбільшими втратами. Однак цей метод прирівнює один до одного цінності всіх видів енергії, зокрема і теплової, що неправильно з позицій другого закону термодинаміки, оскільки будь-який вид енергії може повністю перетворюватись на теплову, зворотний же процес супроводжується неминучими втратами. Використано авторську інноваційну математичну дослідницьку модель впровадженої центральної прямотечійної системи кондиціювання повітря операційних чистих кімнат. Мета моделі – комп’ютерне оцінювання ексергетичної ефективності діючої системи кондиціювання та втрат ексергії в її елементах залежно від різних факторів, що впливають на її роботу. Завдяки цій моделі отримано діаграму Грассмана потоків та втрат ексергії для діючої системи кондиціювання за температури зовнішнього повітря 35 °С.
Оцінювання за діаграмою Грассмана ексергоефективності та втрат ексергії у системі кондиціювання повітря операційних чистих кімнат
Keywords: exergy balance; air conditioning systems; cleanrooms; exergy efficiency; Grassmann diagram; ексергетичний баланс; системи кондиціювання повітря; чисті кімнати; ексергетична ефективність; діаграма Грассмана